Personality and Academic Achievement level in Geography Subject at Secondary level - Guchait, Prity (Future Science / FSH-PH Publications, 2021)
This paper reports a relation between personality and academic achievement in geography subject at secondary level in which sample size is 170 from secondary school of Howrah district. A survey questionnaire was used to gather data. Result reflects that Academic achievement was significantly positive correlated with Extraversion vs. Introversion, Agreeableness vs. Antagonism, Conscientiousness vs. Lack of direction, Neuroticism vs. Emotional stability, and Openness vs. Closedness to experience.